A simplified method for determining the high frequency induction motor equivalent electrical circuit parameters to be used in EMI effect - Riehl, Rudolf Ribeiro [UNESP]; Ruppert Filho, Ernesto (My University, 2007)
The aim of this paper is to present a simple method for determining the high frequency parameters of a three-phase induction motor to be used in studies involving variable speed drives with PWM three-phase inverters, in which it is necessary to check the effects caused to the motor by the electromagnetic interference, (EMI) in the differential mode, as well as in the common mode. The motor parameters determination is generally performed in adequate laboratories using accurate instruments, such as very expensive RLC bridges. The method proposed here consists in the identification of the motor equivalent electrical circuit parameters in rated frequency and in high frequency through characteristic tests in the laboratory, together with the use of characteristic equations and curves, shown in the references to be mentioned for determining the motor high frequency parasite capacitances and also through system simulations using dedicated software, like Pspice, determining the characteristic waveforms involved in the differential and common mode phenomena, comparing and validating the procedure through published papers [01].
Keywords: Electromagnetic interference; Induction motor; Pspice; PWM inverter; Characteristic equations; Common modes; Differential-mode; Electrical machines; Electro magnetic interferences; Equivalent electrical circuits; High frequencies; High-frequency induction; International conferences; Motor parameters; Simple methods; Simplified method; System simulations; Three-phase induction motors; Three-phase inverters; Waveforms; AC motors; Difference equations; Electric drives; Electric network parameters; Electromagnetic compatibility; Electromagnetic pulse; Electromagnetism; Induction motors; Parameter estimation; SPICE; Variable speed drives; Motors